Rational Solutions to the ABS List: Transformation Approach - Zhang, D.; Zhang, D.J. (Symmetry, Integrability and Geometry: Methods and Applications, 2017)
In the paper we derive rational solutions for the lattice potential modified Korteweg-de Vries equation, and Q2, Q1(δ), H3(δ), H2 and H1 in the Adler-Bobenko-Suris list. Bäcklund transformations between these lattice equations are used. All these rational solutions are related to a unified τ function in Casoratian form which obeys a bilinear superposition formula.